Quality of linked data: Linking the National Hospital Care Survey Data to the National Death Index - Lisa Mirel; Dean Resnick; Scott Campbell; Cordell Golden (International Journal of Population Data Science, 2018)
Introduction Data linkages can produce rich data resources to address a variety of research topics. However, assessing linkage quality can be challenging given that there are many approaches and no clear best practices.